2013
DOI: 10.1007/s11274-013-1262-z
|View full text |Cite
|
Sign up to set email alerts
|

Improved cell disruption of Pichia pastoris utilizing aminopropyl magnesium phyllosilicate (AMP) clay

Abstract: An efficient method for Pichia cell disruption that employs an aminopropyl magnesium phyllosilicate (AMP) clay-assisted glass beads mill is presented. AMP clay is functionalized nanocomposite resembling the talc parent structure Si8Mg6O20(OH)4 that has been proven to permeate the bacterial membrane and cause cell lysis. The recombinant capsid protein of cowpea chlorotic mottle virus (CCMV) expressed in Pichia pastoris GS115 was used as demonstration system for their ability of self-assembly into icosahedral vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…(5) aminoclays exhibit antibacterial and antifungal activities under experimental conditions [20] , [21] , which may lower the possibility of bacterial contamination during the transformation procedure. Finally, (6) a further DNA extraction step can be performed in the presence of 0.2 wt% of aminoclay, which facilitates destabilization of cell walls during the bead-beating process [40] .…”
Section: Discussionmentioning
confidence: 99%
“…(5) aminoclays exhibit antibacterial and antifungal activities under experimental conditions [20] , [21] , which may lower the possibility of bacterial contamination during the transformation procedure. Finally, (6) a further DNA extraction step can be performed in the presence of 0.2 wt% of aminoclay, which facilitates destabilization of cell walls during the bead-beating process [40] .…”
Section: Discussionmentioning
confidence: 99%
“…1). This might be due to difficulties in lysis of Pichia cells that possess very complex and rigid cell walls [35]. In particular, a prolonged induction period prevented cell breaking, so the gain of total crude extracts was extremely difficult after 3 days of induction.…”
Section: Discussionmentioning
confidence: 99%
“…It has previously been reported that protein yields above 20 mg ml −1 are required for productive CFPS (Fujiwara & Doi, 2016). As P. pastoris is difficult to lyse (Kim, Wu, Kim, Kim, & Shin, 2013;Stowers & Boczko, 2007), we investigated a variety of methods to determine their suitability for extract preparation. The optimal method would lead to a low number of unlysed, viable cells, without requiring unnecessary dilution (i.e.…”
Section: Optimal Conditions For Harvest and Lysismentioning
confidence: 99%